Simetría y Degeneración: partícula atrapada en una caja cúbica con paredes impenetrables - Hernández-Castillo, A.O.; Lemus, R. (Revista Mexicana de Física E, 2015)
In physics as well as in chemistry the importance of symmetry iswidely acknowledged. It is of common knowledge that the systems'degeneracy, in the domain of linear physical systems, is tightlyrelated with symmetry. The stationary state degeneracy shouldcorrespond with the dimension of the symmetry group irreduciblerepresentations (irreps) associated. Therefore identifying thesymmetry group is essential for labeling the energy levels.Sometimes the spectrum presents systematic accidental degeneracy,which means that the supposed symmetry group is actually a subgroup.This is the case for a particle in a cubic box, with impenetrablewalls. This article presents the procedure that allows theidentification of the new symmetry group that explains thedegeneracy. Furthermore examples to illustrate the concepts arepresented as well as the consequences implied in the selectionrules.